Evaluation of a Cascaded Deep Learning–based Algorithm for Prostate Lesion Detection at Biparametric MRI - Lin, Yue; Yilmaz, Enis C.; Belue, Mason J.; Harmon, Stephanie A.; Tetreault, Jesse; Phelps, Tim E.; Merriman, Katie M.; Hazen, Lindsey; Garcia, Charisse; Yang, Dong; Xu, Ziyue; Lay, Nathan S.; et al. (Radiology, 2024)
A deep learning–based algorithm automatically detected cancerous lesions on prostate biparametric MRI scans with reasonable performance and reliably predicted clinically significant prostate cancer at biopsy.